Translator and interpreter training. Curriculum design. New prospects and dilemmas - Kwieciński, Piotr; Feder, Marcin (Glottodidactica, 2005)
Institutional changes within universities and the challenge of EU enlargement present translator and interpreter trainers with both new opportunities and dilemmas. The major potential tension areas that must be addressed in the curricula include the status of retour translation and interpreting, the role of liaison interpreting in the curriculum, the separation of interpreter and translator training, and the focus on skills and techniques vs. background knowledge. The article suggests tentative solutions in these areas, based on the authors' own experience in curriculum design. The limitations and advantages of a postgraduate training programme within a foreignlanguage department are also discussed.